2019
DOI: 10.1016/j.neuroimage.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model of spread of Parkinson's pathology using network diffusion

Abstract: Growing evidence suggests that a "prion-like" mechanism underlies the pathogenesis of many neurodegenerative disorders, including Parkinson's disease (PD). We extend and tailor previously developed quantitative and predictive network diffusion model (NDM) to PD, by specifically modeling the trans-neuronal spread of alpha-synuclein outward from the substantia nigra (SN). The model demonstrated the spatial and temporal patterns of PD from neuropathological and neuroimaging studies and was statistically validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
84
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 53 publications
6
84
1
1
Order By: Relevance
“…The NDM framework was also recently used for capturing the spatiotemporal progression of Parkinson's disease. 9,11 These studies revealed that the substantia nigra was the most likely seed region, highlighting its role as one of the most atrophied and Lewy-body-rich regions in Parkinson's disease. Another interesting finding was that the temporal sequencing of the regions predicted by the NDM was in close correspondence with the Braak's Lewy-bodybased staging scheme.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The NDM framework was also recently used for capturing the spatiotemporal progression of Parkinson's disease. 9,11 These studies revealed that the substantia nigra was the most likely seed region, highlighting its role as one of the most atrophied and Lewy-body-rich regions in Parkinson's disease. Another interesting finding was that the temporal sequencing of the regions predicted by the NDM was in close correspondence with the Braak's Lewy-bodybased staging scheme.…”
Section: Introductionmentioning
confidence: 99%
“…The present study employed a model of spread of pathology via brain networks based on the network diffusion model (NDM) . A growing number of studies have utilized NDM as a means to model the progression of neurodegenerative pathology on brain networks . Using longitudinal data from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database, Torok and colleagues (2018) showed that NDM and an inference optimization algorithm can successfully infer the regions of disease initiation (referred as seed regions) from which Alzheimer’s disease or Mild Cognitive Impairment tau pathology most likely originated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple lines of evidence have suggested that pathology propagates from a small number of early disease sites along neural connectivity pathways (Desplats et al, 2009;Luk et al, 2012), ultimately affecting most of the brain. Previous work using network diffusion modelling (NDM) has shown that this process can be described by considering the spread of pathology as a diffusion process on the structural connectome (Raj et al, 2012;Pandya et al, 2019), with grey matter atrophy serving as a measure of local pathology. By seeding NDM pathology at every possible brain region, and comparing NDM predictions of atrophy with the true atrophy map, the regional origin of pathology can be inferred (Torok et al, 2018;Pandya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%